One-pot hydrothermal synthesis of strontium titanate nanoparticles photoelectrode using electrophoretic deposition for enhancing photoelectrochemical water splitting - Phoon, Bao Lee; Lai, Chin Wei; Pan, Guan Ting; Yang, Thomas Chung Kuang; Juan, Joon Ching (Elsevier, 2018)
Water splitting is a key target for the development of sustainable hydrogen economy for the future energy system. The formation and deposition of strontium titanate (STO) nanoparticles on fluorine-doped tin oxide (FTO) glass is essential to achieve high efficiency in photoelectrochemical (PEC) water splitting application. In the present study, STO crystalline nanoparticles with a diameter range of 30–56 nm were successfully prepared by using the hydrothermal technique by varying the temperatures from 60 °C to 180 °C. Based on the results, the morphology of perovskite-type STO was significantly influenced by hydrothermal reaction temperature and it was found that the sample STO-150 exhibited the highest PEC water splitting performance with a photocurrent density of 0.65 mA/cm2 under UV irradiation. This was attributed to the uniform nanoparticle size (ca. 47 nm) and the large BET surface area (17.00 m2/g). Next, the hydrothermal synthesised STO nanoparticles were successfully deposited onto a FTO by using electrophoretic deposition (EPD). Interestingly, the STO nanoparticles photoelectrode deposited at 40 V for 120 s exhibited the highest photocurrent density of 1.05 mA/cm2. This is because the STO nanoparticles have a good uniformity with the film thickness of 18.8 µm on FTO glass. It was shown that the deposition voltage and thickness play an important role because the packing density of films may affect the electron transferring pathway. The optimised STO nanoparticles photoelectrode was applied to the PEC water splitting performance testing. Based on the outcome, the hydrogen generation rate was found to be 0.25 mL/cm2 in an hour and able to be re-used continuously for at least five cycles.